Warships - MacKenzie, Iain. (Hauppauge, NY : Barron's Educational Series, 1998)
Highlights the history of warships, from the galleys of the ancient world to modern nuclear-powered aircraft carriers.
Cover title: History of warships.
Includes index.
Keywords: Warships -- Juvenile literature; Warships; Warships